Is Being Emotionally Inexpressive Cool?. Issue 4 (25th March 2018) - Warren, Caleb; Pezzuti, Todd; Koley, Shruti
Abstract : Despite a recognition that consumers want to be cool and value cool brands, the literature has only just begun to delineate what makes things cool. Writing by scholars, quotes by celebrities, and norms in fashion advertising are consistent with the view that people become cool by being emotionally inexpressive. The relationship between emotional expression and coolness, however, has not been empirically tested. Our research uses an experimental approach to examine whether being emotionally inexpressive makes people seem more or less cool than smiling. In contrast to the belief that being inexpressive is cool, we find that in noncompetitive contexts—an endorser in a clothing advertisement and an athlete interacting with fans—being inexpressive makes people seem cold rather than cool. On the other hand, in competitive contexts—such as an athlete facing his opponent—being inexpressive makes people seem cool by making them appear dominant. Our results have important implications for marketers, advertisers, and consumers trying to cultivate a cool image.